SUBSTITUSI KONSENTRAT DENGAN SILASE CAMPURAN HIJAUAN KETELA POHON (Manihot esculenta, Crantz) DAN GLIRISIDIA (Gliricidia sepium, Jacq.) DALAM PAKAN TERHADAP PENAMPILAN DOMBA EKOR GEMUK (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2010)
The aim of this research was to study the effects of concentrates subtitution with cassava leaf (Manihot esculenta, Crantz) and gliricidia (Gliricidia sepium,Jacq) mixtures silage on feed consumption, digestibility, N retention and average daily gain of fat tailed sheep. Twenty  male fat tailed sheep of approximately 18 months, with body weights of 23,85±4.75 kg were alloted randomly into a Randomized Block Designs with five treatments and four blocks. They were kept in the wooden metabolizable cages. The  diets were consisted of  corn leaf (CL), concentrates (C) containing 22,85% crude protein (CP) and cassava leaf-gliricidia mixtures silage (S). The ratio of S : C was 60  : 40% on dry matter (DM) basis. Five dietary treatments were : R0 = CL 60% and C 40% (C 100%  and S 0%); R25 = CL 60% and C 40% (C75% and S 25%); R50 = CL 60% and C 40% (C 50% and S 50%); R75 =Cl 60% and C 40% (C 25% and S 75%); R100 = CL 60% and C 40% (C 0% and S 100%).  The diet was offered at 3% of body weight on the DM basis. The variables measured were DM intake, organic matter (OM)  intake (OM intake), CP intake, DM digestibility, OM digestibility, CP digestibility, DM digestibility intake, OM digestibility intake, CP digestibility intake, N retention and average daily gain (ADG). The results showed that the treatments had no significant differences (P>0.05) on CP intake, but had significant differences (P<0.05) on DM intake, OM intake, N retention  and had highly significant differences (P<0.01) on DM digestibility, OM digestibility, CP digestibility, DM digestibility intake, OM digestibility intake, CP digestibility intake, and ADG. The effects of concentrates substition with silage mixtures till 100% could decrease feed intake, digestibility, N retention and ADG. However, concentrate subtitution with 25% of cassava leaf–gliricidia silage mixtures in the diet showed the same ADG (165.24 g/head/day) with 100% concentrates (168.9 g/head/day). (JIIPB 2010 Vol 20 No 1: 22-30).   Keywords : cassava leaf-gliricidia mixtures silage, concentrates, substitution, fat tailed sheep performance.